A computationally efficient centralized group key distribution protocol for secure multicast communications based upon RSA public key cryptosystem - Vinod Kumar; Rajendra Kumar; S.K. Pandey (Journal of King Saud University. Computer and information sciences, 2020)
In the secure multicast communication, data is transmitted in such a manner that only authorized group members are able to receive the data. The main challenging issue in dynamic and secure multicast communication is to design a centralized group key distribution protocol with minimum computation and storages complexity. This paper, proposes a more efficient centralized group key distribution (CGKD) protocol that minimizes the computation cost of key server (KS) during key updating. The computation cost of members is balanced during key recovery. This reduction in computation cost of KS is achieved by performing one addition, one multiplication and one encryption during single member join and one subtraction, one division and one encryption during a single member leave operation. Moreover, the storage complexity of KS is also minimized. Further, this paper also proposes an extended CGKD protocol based on clustered tree which is very scalable and efficient to deal with enormous membership changes. By comparing with existing similar protocols, the proposed protocol has significantly reduced computation and storage complexity of KS while maintaining less and balanced communication overhead of KS and storage load of each group member. The proposed protocol is implemented and tested on key-star and cluster tree based structure. The experimental results show that the proposed protocol is efficient in terms of computational overhead of KS and group members.